BRZRKR - Vol 1 Volume one - Reeves, Keanu; Kindt, Matt; Garney, Ron; Crabtree, Bill (Comic book colorist); Robins, Clem, 1955- (Los Angeles : BOOM! Studios, 2021)
"The man known only as B. is half-mortal and half-God, cursed and compelled to violence...even at the sacrifice of his sanity. But after wandering the world for centuries, the Berzerker may have finally found a refuge working for the U.S. government to fight the battles too violent and too dangerous for anyone else. In exchange, B. will be granted the one thing he desires - the truth about his endless blood-soaked existenceand how to end it."--Provided by publisher.
Keywords: Immortality -- Comic books, strips, etc; Imaginary wars and battles -- Comic books, strips, etc; Violence -- Comic books, strips, etc; Comics (Graphic works); Science fiction comics